Lesion Size Is a Predictor of Clinical Outcomes After Bone Marrow Stimulation for Osteochondral Lesions of the Talus: A Systematic Review. (June 2017) - Ramponi, Laura; Yasui, Youichi; Murawski, Christopher D.; Ferkel, Richard D.; DiGiovanni, Christopher W.; Kerkhoffs, Gino M.M.J.; Calder, James D.F.; Takao, Masato; Vannini, Francesca; Choi, Woo Jin; Lee, Jin Woo; Stone, James; et al.
Background: The critical lesion size treated with bone marrow stimulation (BMS) for osteochondral lesions of the talus (OLTs) has been 150 mm 2 in area or 15 mm in diameter. However, recent investigations have failed to detect a significant correlation between the lesion size and clinical outcomes after BMS for OLTs. Purpose: To systematically review clinical studies reporting both the lesion size and clinical outcomes after BMS for OLTs. Study Design: Systematic review. Methods: A systematic search of the MEDLINE and EMBASE databases was performed in March 2015 based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Included studies were evaluated with regard to the level of evidence (LOE), quality of evidence (QOE), lesion size, and clinical outcomes. Results: Twenty-five studies with 1868 ankles were included; 88% were either LOE 3 or 4, and 96% did not have good QOE. The mean area was 103.8 ± 10.2 mm 2 in 20 studies, and the mean diameter was 10.0 ± 3.2 mm in 5 studies. The mean American Orthopaedic Foot and Ankle Society score improved from 62.4 ± 7.9 preoperatively to 83.9 ± 9.2 at a mean 54.1-month follow-up in 14 studies reporting both preoperative and postoperative scores with a mean follow-up of more than 2 years. A significant correlation was found in 3 studies, with a mean lesion area of 107.4 ± 10.4 mm 2, while none was reported in 8 studies, with a mean lesion area of 85.3 ± 9.2 mm 2 . The lesion diameter significantly correlated with clinical outcomes in 2 studies (mean diameter, 10.2 ± 3.2 mm), whereas none was found in 2 studies (mean diameter, 8.8 ± 0.0 mm). However, the reported lesion size measurement method and evaluation method of clinical outcomes widely varied among the studies. Conclusion: An assessment of the currently available data does suggest that BMS may best be reserved for OLT sizes less than 107.4 mm 2 in area and/or 10.2 mm in diameter. Future development in legitimate prognostic size guidelines based on high-quality evidence that correlate with outcomes will surely provide patients with the best potential for successful long-term outcomes.